2020
DOI: 10.1111/jfb.14580
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns and habitat associations ofSandelia bainsii(Teleostei:Anabantidae), a highly threatened narrow‐range endemic freshwater fish

Abstract: Sandelia bainsiiis a range‐restricted and highly threatened freshwater fish endemic to South Africa. Recent genetic evidence suggests that this species comprises three allopatrically distributed lineages that have been informally designated asSandeliasp. “Kowie,”Sandeliasp. “Keiskamma” andSandeliasp. “Buffalo.” As these lineages have only been recently identified and are likely to face a high risk of extinction because of restricted distributions, there is a critical need for generating ecological information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
0
11
0
2
Order By: Relevance
“…Abiotic factors such as the in situ physico-chemical parameters, habitat heterogeneity and biotic interactions including competition and predation affect the spatial distribution of fish species in their environment (Karr, 1981). For example, in the Great Fish River system, Sifundza et al (2021) showed a negative association between the endangered native Eastern Cape Rocky Sandelia bainsii and the presence of non-native predatory species Largemouth Bass Micropterus salmoides and African Sharptooth Catfish Clarias gariepinus. Similarly, MacRae and Jackson (2001) demonstrated that in small lakes ( 50 ha) in central Ontario, the presence of the non-native predatory Smallmouth Bass Micropterus dolomieu drives small cyprinids to predominantly utilise complex and specific habitats whereas, in lakes without Smallmouth Bass the cyprinids inhabited a more diverse range of habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic factors such as the in situ physico-chemical parameters, habitat heterogeneity and biotic interactions including competition and predation affect the spatial distribution of fish species in their environment (Karr, 1981). For example, in the Great Fish River system, Sifundza et al (2021) showed a negative association between the endangered native Eastern Cape Rocky Sandelia bainsii and the presence of non-native predatory species Largemouth Bass Micropterus salmoides and African Sharptooth Catfish Clarias gariepinus. Similarly, MacRae and Jackson (2001) demonstrated that in small lakes ( 50 ha) in central Ontario, the presence of the non-native predatory Smallmouth Bass Micropterus dolomieu drives small cyprinids to predominantly utilise complex and specific habitats whereas, in lakes without Smallmouth Bass the cyprinids inhabited a more diverse range of habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Lake fisheries are particularly vulnerable to environmental changes (Venard and Scarnecchia, 2005). In particular, fish distribution is usually limited by environment temperature (Missaghi et al, 2017), water quality (Araujo et al, 2018), ecosystem structure (Ferrari et al, 2018), and other external distractions (Weijerman et al, 2019;Sifundza et al, 2021). In addition, different phases of the fish life cycle, including spawning, feeding, nursery, and migrations, require specific environmental conditions, involving a series of complicated driving factors (Petitgas et al, 2006;Giannoulaki et al, 2017;Sólmundsson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Estos son una fuente de información sólida para comprender la distribución actual de las especies de peces de agua dulce (Asase et al, 2021, Comte et al, 2013 y evaluar los cambios en escenarios climáticos presentes y futuros en ausencia de datos ecológicos (Guisan et al, 2017;Townsend-Peterson et al, 2011;Zhang et al, 2019;Zurell et al, 2020). De modo que cada vez son más utilizados en ecosistemas marinos y continentales (Aksu, 2021;Alexandre da Silva et al, 2019;Barragán-Barrera et al, 2019;Lucifora et al, 2015;McNyset, 2005;Sifundza et al, 2021;Taylor et al, 2017;Yousefi et al, 2020). Sin embargo, pocos estudios se han centrado en especies endémicas (Aksu, 2021;Hopkins & Burr, 2009;Sifundza et al, 2021;Yousefi et al, 2020), especialmente en el Neotrópico; región donde las especies más susceptibles al cambio climático muestran patrones geográficos claros (Foden et al, 2008), como el hemisferio sur donde las mayores proporciones de riqueza de especies fluviales representa una proporción importante a escala continental en relación con otras zonas como África y Centroamérica (Oberdorff et al, 2011).…”
Section: Introductionunclassified
“…De modo que cada vez son más utilizados en ecosistemas marinos y continentales (Aksu, 2021;Alexandre da Silva et al, 2019;Barragán-Barrera et al, 2019;Lucifora et al, 2015;McNyset, 2005;Sifundza et al, 2021;Taylor et al, 2017;Yousefi et al, 2020). Sin embargo, pocos estudios se han centrado en especies endémicas (Aksu, 2021;Hopkins & Burr, 2009;Sifundza et al, 2021;Yousefi et al, 2020), especialmente en el Neotrópico; región donde las especies más susceptibles al cambio climático muestran patrones geográficos claros (Foden et al, 2008), como el hemisferio sur donde las mayores proporciones de riqueza de especies fluviales representa una proporción importante a escala continental en relación con otras zonas como África y Centroamérica (Oberdorff et al, 2011). Chortiheros wesseli (Miller, 1996) y Amphilophus hogaboomorum (Carr y Giovannoli, 1950) son las únicas dos especies de cíclidos endémicos de Honduras descritas formalmente (Matamoros et al, 2009) y se encuentran incluidas en la lista de especies de preocupación especial de Honduras (Secretaría de Recursos Naturales y Ambiente, SERNA, 2008).…”
Section: Introductionunclassified